Investigating the role of mobile network operators as platform providers in the internet of things - Athanasios Karapantelakis; Jan Markendahl (International Telecommunications Society (ITS), 2015)
Internet of Things (IoT) is generally understood to be a realisation of the vision of ubiquitous computing, wherein any type of device will be connected to the Internet and will be controlled by remote software. The transition of Information and Communication Technology (ICT) ecosystem towards IoT is set to happen gradually over the next decade, with multiple independent sources predicting at least an order of magnitude increase in data traffic to and from connected devices. In particular, Mobile Network Operators (MNOs) are set to play an instrumental role in the IoT economy of the future, with the emergence of fifth generation mobile networks (5G). The transition to IoT, however, poses multiple challenges for MNOs who have to serve a large market of many industry segments (e.g. utilities, transport, agriculture), while simultaneously face commoditisation of their core services (i.e. voice, messaging and mobile broadband). In order to survive and thrive in the IoT economy, MNOs need to reconsider their role by repositioning themselves in the value chain. This paper, inspired from platform economics and successful examples of multi-sided platforms in the Information Technology (IT) industry, suggests a role of MNOs as mediators in a multi-sided market, connecting billions of devices on one end of the market with software providers on another end. The value of this idea is discussed by presentation of several prototypes that utilise MNO as a service provider
Keywords: 330